The Skill Profile of Pre-Service Science Teachers In Writing Strem-Based (Science-Technology-Religion-Engineering-Mathematics) Science Teaching Materials - Wahyuni Handayani; Tri Wahyu Agustina; Muhammad Ghilman Firdaus (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
This study aims to identify the profile of STREM-based science writing skills in pre-service science teachers. The study was done using a descriptive method through a study of STREM-based science teaching materials documentation written by the pre-service science teachers. The target population is the seventh-semester students. Fifty people who are enrolled in the elective course of Integrated Science Learning were selected through Purposive Sampling. Performance assessment of the STREM-based science teaching materials was done using an analytical rubric with a score of 1-4 on the aspect of pedagogic, content, and context. Determination of inter-rater reliability was taken from 25 random samples of teaching materials and correlated their scores using Pearson's correlation. The inter-rater reliability score obtained is 0.938 in all aspects of teaching materials; 0.690 in the pedagogic aspect; 0.976 in the aspect of content; and 0.921 in the context aspect. The score of the teaching materials is then converted in the form of a percentage and interpreted based on certain criteria. The average score of pre-service science teachers' writing skills was 53.3% in the